Windows of opportunities and knowledge networks: implications for the catch-up in developing countries - Melo, Marne Santos de (2016)
This document represents a doctoral thesis held under the Brazilian School of Public and Business Administration of Getulio Vargas Foundation (EBAPE/FGV), developed through the elaboration of three articles. The research that resulted in the articles is within the scope of the project entitled 'Windows of opportunities and knowledge networks: implications for catch-up in developing countries', funded by Support Programme for Research and Academic Production of Faculty (ProPesquisa) of Brazilian School of Public and Business Administration (EBAPE) of Getulio Vargas Foundation.